Inhibition of Proinflammatory Cytokines in Cutibacterium acnes-Induced Inflammation in HaCaT Cells by Using Buddleja davidii Aqueous Extract. (21st April 2020) - Nguyen, Anh Thu; Kim, Ki-young
Abstract : Acne is an inflammatory skin disorder; although some anti-inflammatory medicines for treating acne are available in a market, they have considerable side effects; therefore, new treatment options are needed. In the present study, among the 16 aqueous extracts of plants collected from Jeju Island in Korea which are used to test anti-inflammatory activity, B. davidii showed the strong decline of the proinflammatory cytokine expression against the inflammatory process caused by C. acnes in Human HaCaT keratinocyte cells. B. davidii downregulated the expression of 57% of COX-2, 41% of iNOS, and proinflammatory cytokines 29% of TNF- α, 32% of IL-1 β, 21% of IL-6, and 35% of IL-8. Furthermore, B. davidii inhibited NF- κ B and MAPK signaling cascades in keratinocytes that activated by toll-like receptor 2 (TLR-2) in response to C. acnes . Given those results, B. davidii is a potential agent to reduce the proinflammatory cytokine expression against C. acnes -induced inflammation and might provide an alternative to the current medications.